2016
DOI: 10.4067/s0717-97072016000300007
|View full text |Cite
|
Sign up to set email alerts
|

A Greener Approach for the Degradation of Dye Methylene Blue by Organic Additive Catalysed Photo - Fenton Process

Abstract: Fenton and photo-Fenton processes are proven to be most promising techniques for the wastewater treatment methods. It provides an attractive method for degradation of dyes and breaks them into simple mineral form. These are cost effective and ecologically viable techniques with additional advantages of relatively simple approach, use of less hazards chemicals for the degradation and cyclic nature. Thus, it serves as a green chemical and eco-friendly pathway in reducing pollution caused by complex dye molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Abhilasha et al, using photo Fenton reaction, removed MB dye under the light. In their research, they determined that 2.33 × 10 -5 M dyestuff was the optimum paint removal amount (Abhilasha 2016).…”
Section: Optimum Mb Dye Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Abhilasha et al, using photo Fenton reaction, removed MB dye under the light. In their research, they determined that 2.33 × 10 -5 M dyestuff was the optimum paint removal amount (Abhilasha 2016).…”
Section: Optimum Mb Dye Concentrationmentioning
confidence: 99%
“…At the end of the research, it was determined that the optimum H 2 O 2 concentration was reached by using 20 mg/L (600 µL of 30% H 2 O 2 ). Abhilasha et al showed in their research that they use 130 µL (30%) H 2 O 2 (Abhilasha 2016). Ayodamope studied the amount of H 2 O 2 in the range of 50-200 mg/L in their study and found that the most suitable concentration is 100 mg/L (Ayodamope 2015).…”
Section: Determination Of Optimum Peroxide Concentrationmentioning
confidence: 99%
“…The second stage of reaction is dominated with a significant decrease in absorbance. This stage represents degradation reaction where OH radicals mineralize the dye molecules [16]. The degradation of 0.0188 M (50 mL) dye solution obtained after treatment of dye with Fe 3 O 4 and Ag-Fe 3 O 4 for 120 min was 41 and 73%, respectively.…”
Section: Catalytic Activity Of Synthesized Fe 3 O 4 and Ag-fe 3 Omentioning
confidence: 99%
“…Many advanced oxidation processes (AOPs), with various approaches including H 2 O 2 /Fenton, UV/TiO 2 , O 3 /H 2 O 2 , UV/ H 2 O 2 , UV/O 3 , ozonation have been studied for the treatment of organic dyes from wastewater [15][16][17]. AOPs are known to generate hydroxyl radical (HO), which is well known as a powerful oxidant with an oxidation potential of around 2.86 V [12,17,18].…”
Section: Introductionmentioning
confidence: 99%